Comparative efficacy of acupuncture-related techniques for mild cognitive impairment: A Bayesian network analysis - Li, Xin; Lai, Lanfeng; Lu, Liming; Yan, Liang; Deng, Kelin; Li, ZhiMing; Xu, Nenggui; Zhao, JiaYing (Frontiers in Neurology, 2022)
Background: To compare and rank the clinical effects of various acupuncture and acupuncture-related therapy on mild cognitive impairment patients. Methods: Using network meta-analysis, we assessed the direct and indirect evidence from relevant research. Seven databases (PubMed; Web of Science, Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI); VIP Database and Wanfang database.) were examined in order to ﬁnd randomized controlled trials of acupuncture-related therapies for individuals with mild cognitive impairment. The data were analyzed using Stata15.0 and R3.6.1 software after two researchers independently scanned the literature, retrieved the data, and evaluated the risk of bias in the included studies. Results: A total of 27 randomized controlled trials involving 2,210 patients were included. Bayesian NMA showed that manual acupuncture combined with Conventional Therapy, moxibustion combined with conventional therapy, manual acupuncture and electroacupuncture were most effective in improving MMSE score. The most effective interventions for MoCA score were moxibustion combined with Conventional Therapy, followed by manual acupuncture combined with conventional therapy, acupressure combined with conventional therapy and manual acupuncture combined with moxibustion. Manual acupuncture combined with moxibustion was dominant in the cluster ranking. The results of the node splitting method revealed that direct and indirect evidence were consistent (P > 0.05). In addition, publication bias was detected. Conclusion: This research will add to the body of knowledge about the safety and efficacy of acupuncture-related therapies in the treatment of mild cognitive impairment, and it could aid clinical guideline builders choose the optimum acupuncture treatment for mild cognitive impairment.